Group consumption and product diversity: the case of smoking bans - Foucart, Renaud (Wiley, 2017)
I study product diversity in the presence of search costs and groups of consumers. Groups with heterogeneous tastes create a leverage effect on competition: a large majority of firms may end up offering a product that corresponds to the taste of the minority. I illustrate this idea with smoking bans in bars and restaurants. When the first nonsmoking restaurants opened, there were few of them with little competition and high market power on nonsmokers. By extracting a large surplus from nonsmokers, nonsmoking restaurants became unattractive to other groups, while smoking restaurants were plenty and competitive, attracting both smokers and mixed groups.